PENGEMBANGAN SISTEM E-LEARNING BERBASIS MOODLE DI SMK N 3 PARIAMAN - Santi Sartika; Ami Anggraini Samudra; Haris Kurniawan (STMIK KAPUTAMA, 2023)
The purpose of this study is the development of an E-Learning system as a learning medium at SMK N 3 Pariaman. The research on developing a moodle-based e-learning system at SMK N 3 Pariaman is based on the moodle method of R&D (Research and Development). This research uses research and development (R&D) methods. Research and development Research and development (R&D) is a research method used to produce certain products, and test the effectiveness of these products. The research and development procedure basically consists of two main objectives, namely: developing the product, and testing the effectiveness of the product in achieving the goal. The first objective is referred to as the bearer function while the second objective is referred to as validation. The results of this research development of a Moodle-based Learning Management System (LMS) which has been conducted a Moodle-based Learning Management System (LMS) Validity Test at SMK N 3 Pariaman, states that a Moodle-based Learning Management System (LMS) with a material validation test value of 0.709% and a value of 0.709%. media validation test 0.780% declared valid.